Pengaruh Konten Media Sosial Instagram Dealer Honda Jakarta Center dan Ulasan Pelanggan pada Google Review Terhadap Keputusan Pembelian Melalui Kepercayaan Pelanggan pada Bengkel HJC Retail - Zuhria Nirahai; Istiharini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to measure the influence of social media content and customer reviews on purchase decisions through trust as an intervening variable. The total number of respondents in this study is 108 individuals who are customers of the Honda Jakarta Center workshop, have Instagram accounts, and follow the official Instagram account of Honda Jakarta Center. Data analysis in this research was conducted using the PLS 3.0 tool. The results of the study indicate that social media content influences trust, customer reviews influence trust, social media content influences purchase decisions, customer reviews influence purchase decisions, and trust mediates the relationship between both social media content and customer reviews with purchase decisions.